Teacher training for the implementation of digital information and communication technologies in a presential context (Research, Society and Development, 2021)
With the growing interest of the educational community in the digital literacy of students and teachers, in this article we seek to understand the daily challenges faced by teachers to implement the use of digital information and communication technologies - TDIC - in the teaching and learning process of Portuguese Language, in the public school, in face-to-face format. This is a qualitative study, descriptive and explanatory in nature, with field research subsidized by the application of a semi-structured interview and non-participatory observation recorded in a field notebook. We draw on contributions from Vygotsky (1991) on interaction in learning; the studies by Nóvoa (2007) on teacher education; the contributions of Coscarelli (2014, 2016) on digital literacy and the considerations of Alcântara and Lima (2019) about technology as a pedagogical resource. The results found so far have shown that, although there were structural challenges, in terms of teacher training and of a pedagogical nature, the digital literacy of educators, in the process of continuing education at school, expanded the possibilities of working with digital technologies.